Improved separation and size characterization of gold nanoparticles through a novel capillary zone electrophoresis method using poly(sodium4‐styrenesulfonate) as stabiliser and a stepwise field strength gradient. Issue 6 (9th January 2017) - Ciriello, Rosanna; Iallorenzi, Pina Teresa; Laurita, Alessandro; Guerrieri, Antonio
Abstract : A novel capillary zone electrophoresis (CZE) method was developed for an improved separation and size characterization of pristine gold nanoparticles (AuNP) using uncoated fused‐silica capillaries with UV‐Vis detection at 520 nm. To avoid colloid aggregation and/or adsorption during runs, poly(sodium 4‐styrenesulfonate) (PSS) was added (1%, w/v) in the running buffer (CAPS 10 mM, pH 11). This polyelectrolyte conferred an enhanced stabilization to AuNP, both steric and electrostatic, exalting at the same time their differences in electrophoretic mobility. Resolution was further and successfully improved through a stepwise field strength gradient by the application of 25 kV for the first 5 min and then 10 kV. Migration times varied linearly with particles diameters showing relative standard deviations better than 1% for daily experiments and 3% for interday experiments. A comparison with the size distribution obtained by transmission electron microscopy (TEM) allowed assessing that the electrophoretic profile can reasonably be considered as representative of the effective size heterogeneity of each colloid. Finally, the practical utility of the proposed method was demonstrated by measuring the core diameter of a gold colloid sample produced by chemical synthesis which was in good agreement with the value obtained by TEM measurements.